2020
DOI: 10.1017/s2045796020000803
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network activity in bipolar disorder

Abstract: Since its discovery in 1997, the default mode network (DMN) and its components have been extensively studied in both healthy individuals and psychiatric patients. Several studies have investigated possible DMN alterations in specific mental conditions such as bipolar disorder (BD). In this review, we describe current evidence from resting-state functional magnetic resonance imaging studies with the aim to understand possible changes in the functioning of the DMN in BD. Overall, several types of analyses includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…As shown in Table 1, resting-state fMRI studies have revealed altered GS topography in several psychiatric and neurological disorders. Similar to abnormal brain regions in classic FC analysis (Kaiser et al, 2015;Li et al, 2018;Syan et al, 2018;Yan et al, 2019;Zovetti et al, 2020), altered GS topography is mainly located in higher-order association networks (such as the DMN, limbic affective network, frontoparietal network, and salience network), with a relatively small part in the sensorimotor network. However, there may be different pathological mechanisms indicated by GS topography and classic FC.…”
Section: Pathological Significance Of the Gs Topographymentioning
confidence: 80%
“…As shown in Table 1, resting-state fMRI studies have revealed altered GS topography in several psychiatric and neurological disorders. Similar to abnormal brain regions in classic FC analysis (Kaiser et al, 2015;Li et al, 2018;Syan et al, 2018;Yan et al, 2019;Zovetti et al, 2020), altered GS topography is mainly located in higher-order association networks (such as the DMN, limbic affective network, frontoparietal network, and salience network), with a relatively small part in the sensorimotor network. However, there may be different pathological mechanisms indicated by GS topography and classic FC.…”
Section: Pathological Significance Of the Gs Topographymentioning
confidence: 80%
“…The precuneus/PCC and mPFC are major hub nodes of the default-mode network (DMN), which is involved in multiple cognitive and affective functions such as emotional processing, self-referential mental activity, distraction and recollection of experiences, and possibly exerts a modulatory role during attention-requiring tasks (Raichle, 2015). Aberrant activity and connectivity within the DMN are well-documented in different mood states of BD (Syan et al, 2018; Vargas et al, 2013; Wang et al, 2020; Zovetti et al, 2020). For example, previous studies found that hypo-connectivity between the anterior and posterior DMN in manic BD patients might be related to an attention pattern that is excessively focused on external stimuli at the expense of internal reflection (Magioncalda et al, 2015; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for affective influences on DMN activity and its interaction with other networks comes from several observations (Buckner and DiNicola, 2019;Kaiser et al, 2015), but their functional significance remains unresolved. A down-regulation of within-DMN connectivity was reported in healthy participants during sad mood induction through self-generated memories (Harrison et al, 2008) or movies (Borchardt et al, 2018), while disturbances of DMN connectivity are observed in clinical mood disorders such as depression and bipolar disease (Rey et al, 2014;Zovetti et al, 2020). Dynamic shifts in the balance between DMN and SN are also thought to mediate adaptive responses to acute stressors, promoting higher vigilance and fear (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%